Real Interest Rate and Investment Nexus: The Case of Ghana (Global Journal of Management and Business Research, 2018)
This study examines variations in interest rate and investment determination in Ghana. The study is necessitated by the fact that previous studies only examined the effect of interest rate on investment determination without assessing the bi-casual relationship between these macroeconomic variables. Investment decision is seen as demand for credit in an economy and this study calculated the annual time series for the period 1990-2014 and examined the determinants of interest rate variation and its impact on investment. Unit roots and co-integration tests were conducted. Data for the study were extracted from the World Development Indicators Database. The study revealed that variation in interest rate played a negative and highly significant role in investment decision in the economy and demand for credit also had negative and significant influence on interest rate variations in both the short run and long run. Although, the study deduced that investment has an indirect relationship with interest rate variation, other variables such as debt burden, economic stability, foreign exchange, shortage and lack of infrastructure affect gross domestic investment. Improvement in these key macro-economic variables is a necessary condition towards promoting investment. The findings and recommendations provide vital information relevant for policy formulation and implementation aimed at boosting investment in Ghana.
Keywords: investment; interest rate; inflation